PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SD - Hadist Awalia Fauzia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This study aims to determine differences in learning outcomes of Mathematics of primary school students using problem based learning model. The type of research used is the meta-analysis of research that has been done before. This research uses quantitative synthesis method. The purpose of this study is to determine the effect of using problem based learning model on elementary mathematics subjects. Data collection in this research is done by searching journal through google scholar. Keywords used for journal search are: improving the results of elementary mathematics learning, problem based learning. From the model of problem based learning selected 10 research results to be analyzed further in% form. Based on the results of the analysis of 10 research results, it can be concluded that the learning with Problem based learning model (PBL) can improve the learning outcomes of learners learner. Increased learning outcomes from the lowest 5% to the highest 40%, with an average of 22.9%.